A Postmortem Study of Blunt Cardiac Injuries (Medico Legal Update, 2019)
Introduction: Blunt cardiac injury (BCI) refers to injury sustained due to blunt trauma to the heart. The manifestations of such range from clinically silent, transient arrhythmias to deadly cardiac wall rupture.Objectives: To study the blunt cardiac trauma following vehicular accidents brought for autopsy to the morgue of Osmania Medical College, Hyderabad have been studied.Method: 55 cases of blunt cardiac trauma following vehicular accidents brought for autopsy to the Department of Forensic Medicine , Osmania Medical College, Hyderabad have been studied to find out types of cardiac injuries, their association with sternal and rib fractures, mechanism of causation, risk factors, etc.Results: It was observed that 60 % of the cases with blunt cardiac trauma had associated sternal and rib fractures. Maximum number (58%) of the cardiac rupture was seen in run-over cases. The right ventricle of the heart was involved in 23 (41%) cases . All the injuries were located on the anterior surface of the heart.Conclusion: In assessing blunt cardiac trauma victims in vehicular accidents, knowledge about the commonest sites, types and degrees of injuries have been highlighted in the present study, which will help in a timely intervention.